Pedogenesis of Mt. Sumbing Volcanic Ash above The Alteration Clay Layer in The Formation of Landslide Susceptible Soils in Bompon Sub-Watershed - Waode Asryanti Wida; Azwar Maas; Junun Sartohadi (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
Numerous researches on landslides have been carried out by many researches. However, studies on soil physical properties related to landslides potential in volcanic area are still rare. The objective of this study was to examine the effect of soil physical properties on landslides potential. To collect the soil sample, sampling area method was applied. The soil type used in this study was the residual soil. The values of clay liquid limit, plasticity limit, plasticity index, water content, COLE index were used to measure the physical properties of the soil. Organic material was used as the supporting data. The results showed that the soil in the command area showed high value of clay which exceeded 50%. Such high level conditions in each profile affect the liquid limit; plasticity limit, plasticity index, water content, COLE index and organic material. Based on the results, it can be concluded that residual soils with significantly high clay values illustrated the risk of landslide fields formation in Bompon sub-watershed. The clay soil layer was the controlled factor of soil movement.